Paleomagnetism of the Miocene Soma basin and its structural implications on the central sector of a crustal-scale transfer zone in western Anatolia (Turkey). (15th May 2020) - Westerweel, Jan; Uzel, Bora; Langereis, Cornelis G.; Kaymakci, Nuretdin; Sözbilir, Hasan
Highlights: The Soma basin lies within the İzmir-Balıkesir Transfer Zone (İBTZ). Two distinct Neogene deformation phases dominated by strike-slip faulting. The Soma basin underwent ~50° CW rotation in the middle Miocene and then ~21° CCW. Slab tearing induced a regional switch from localized to distributed extension. A possible link between the İBTZ and the North Anatolian Fault Zone is firstly identified. Abstract: The İzmir–Balıkesir Transfer Zone (İBTZ) is a crustal-scale major tectonic feature in western Anatolia accommodating differential extension between the Menderes (MCC) and Cycladic (CCC) core complexes. The kinematics and evolution of the southern part of the İBTZ are well constrained, but its northern continuation remains unstudied. This part is crucial in understanding the complete evolution of western Anatolian tectonics, as well as a possible link between the İBTZ and North Anatolian Fault Zone (NAFZ). In this study, new and extensive paleomagnetic, structural, and stratigraphic data were collected from the Soma basin. These results show that the basin evolved as a part of the İBTZ, including two separate rotational phases. During the first (middle Miocene) phase, deformation was characterized by transcurrent tectonics and associated block rotations as much as ~50° clockwise, during which the İBTZ evolved as a wide dextral shear zone. During the second (late Miocene – recent) phase, the mode of deformation in the Aegean region switched from localized to distributed extension, related to the acceleration of the tearing-off of the African Oceanic slab below the Aegean region. This led to the narrowing of the İBTZ as a discrete brittle shear around the Soma basin, manifested by decoupling of dextral strike-slip and normal faulting. In this period, the Soma basin underwent around −21° counter-clockwise rotation. Based on our new results, the İBTZ extends further to the north and possibly interacts with the southern branch of the NAFZ since the late Miocene.